2015
DOI: 10.1080/10408398.2013.766584
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Propionibacteria in Fermented Milks as a Probiotic

Abstract: Propionibacteria are mainly found in dairy products and fermented milks but are found in other foods as well. Dairy propionibacteria have recently shown to exert potential probiotic activities such as production of propionic acid, vitamins, bacteriocins, essential enzymes, and other vital metabolites. Furthermore, stimulating the immune system and lowering the blood cholesterol level are some of their favorable effects. They have a wide spectrum of antimicrobial activities, inhibiting the growth of gram-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 112 publications
1
11
0
Order By: Relevance
“…In addition, stress tolerance of L. casei BL23 and of P. freudenreichii 138 was maintained upon cold storage in skim milk plus WPI. Therefore, the amount of nutrients provided by milk plus WPI was sufficient to sustain survival of the bacteria over 90 days of cold storage, in accordance with previous reports ( Cousin et al, 2012b ; Vargas et al, 2015 ; Moslemi et al, 2016 ; Shori, 2016 ; Baruzzi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, stress tolerance of L. casei BL23 and of P. freudenreichii 138 was maintained upon cold storage in skim milk plus WPI. Therefore, the amount of nutrients provided by milk plus WPI was sufficient to sustain survival of the bacteria over 90 days of cold storage, in accordance with previous reports ( Cousin et al, 2012b ; Vargas et al, 2015 ; Moslemi et al, 2016 ; Shori, 2016 ; Baruzzi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Acetobacter have been identified in other cereal-based fermented foods such as burukutu , a fermented traditional sorghum-based beer (Oguntoyinbo, 2014), while Gluconobacter and Gluconacetobacter are associated with acidic beers (Bokulich and Bamforth, 2013; Mamlouk and Gullo, 2013; Spitaels et al, 2014a). Conversely, Propionibacterium is mainly associated with dairy and fermented dairy products (Moslemi et al, 2016), with some species being able to improve the probiotic properties of lactic acid bacteria when incorporated into the vegetables during the production (fermentation) of sauerkraut and other vegetable salads (Babuchowski et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Animals, plants and fungi are incapable of producing this vitamin, and hence, it is exclusively produced by microorganisms (LeBlanc et al, 2011). It has been demonstrated that cobalamin can be synthesized by some bacteria such as L. reuteri ZJ03, Propionibacterium freudenreichii , B. animalis Bb12 in soy-yogurt, kefir and fermented milk, respectively (Van Wyk et al, 2011; Patel et al, 2013, Gu et al, 2015; Moslemi et al, 2016). Microorganisms can biosynthesize two different isoforms, the vitamin and the pseudovitamin.…”
Section: Biofunctional Foodsmentioning
confidence: 99%